Meropenem Versus Piperacillin-Tazobactam for Definitive Treatment of Bloodstream Infections Caused by AmpC β-Lactamase–Producing Enterobacter spp, Citrobacter freundii, Morganella morganii, Providencia spp, or Serratia marcescens: A Pilot Multicenter Randomized Controlled Trial (MERINO-2). (2nd August 2021) - Stewart, Adam G; Paterson, David L; Young, Barnaby; Lye, David C; Davis, Joshua S; Schneider, Kellie; Yilmaz, Mesut; Dinleyici, Rumeysa; Runnegar, Naomi; Henderson, Andrew; Archuleta, Sophia; Kalimuddin, Shirin; et al.
Abstract: Background: Carbapenems are recommended treatment for serious infections caused by AmpC-producing gram-negative bacteria but can select for carbapenem resistance. Piperacillin-tazobactam may be a suitable alternative. Methods: We enrolled adult patients with bloodstream infection due to chromosomal AmpC producers in a multicenter randomized controlled trial. Patients were assigned 1:1 to receive piperacillin-tazobactam 4.5 g every 6 hours or meropenem 1 g every 8 hours. The primary efficacy outcome was a composite of death, clinical failure, microbiological failure, and microbiological relapse at 30 days. Results: Seventy-two patients underwent randomization and were included in the primary analysis population. Eleven of 38 patients (29%) randomized to piperacillin-tazobactam met the primary outcome compared with 7 of 34 patients (21%) in the meropenem group (risk difference, 8% [95% confidence interval CI, –12% to 28%]). Effects were consistent in an analysis of the per-protocol population. Within the subcomponents of the primary outcome, 5 of 38 (13%) experienced microbiological failure in the piperacillin-tazobactam group compared to 0 of 34 patients (0%) in the meropenem group (risk difference, 13% [95% CI, 2% to 24%]). In contrast, 0% vs 9% of microbiological relapses were seen in the piperacillin-tazobactam and meropenem arms, respectively. Susceptibility to piperacillin-tazobactam and meropenem using broth microdilution was found in 96.5% and 100% of isolates, respectively. The most common AmpC β-lactamase genes identified were bla CMY-2, bla DHA-17, bla CMH-3, and bla ACT-17 . No ESBL, OXA, or other carbapenemase genes were identified. Conclusions: Among patients with bloodstream infection due to AmpC producers, piperacillin-tazobactam may lead to more microbiological failures, although fewer microbiological relapses were seen. Clinical Trials Registration: NCT02437045. Abstract : Among patients with bloodstream infection due to AmpC-producing Enterobacterales, no difference in clinical and microbiological efficacy was observed between piperacillin-tazobactam and meropenem. More microbiological failures occurred in the piperacillin-tazobactam group, although fewer relapses were seen. A larger trial is required.